The role of daratumumab in relapsed/refractory CD38 positive acute leukemias—case report on three cases with a literature review - Prejzner, Witold; Piekoś, Oliwia; Bełdzińska, Karolina; Sadowska-Klasa, Alicja; Zarzycka, Ewa; Bieniaszewska, Maria; Lewandowski, Krzysztof; Zaucha, Jan Maciej (Frontiers in Oncology, 2023)
Primary refractory or relapsed T-cell acute lymphoblastic leukemia (T-ALL) and mixed phenotype myeloid/T-cell acute leukemia have dismal prognoses. New treatment approaches, preferably targeting specific leukemic aberrations to overcome resistance, are urgently needed. The bright expression of the CD38 antigen found in several cases of T-ALL led to an investigation into the role of anti-CD38 antibodies in the treatment of T-ALL. Here, we present three cases of resistant and relapsed T-ALL and myeloid/T-cell treated with daratumumabbased therapy, including venetoclax and bortezomib (Dara-Ven-Bor). All patients achieved complete remission with minimal residual disease negativity within four weeks of treatment,allowing them to proceed to allogeneic hematopoietic cell transplantation. The toxicity of the triple schema was acceptable. Our patients and other cases reviewed here suggest that daratumumab combined with venetoclax and bortezomib may be a very effective and relatively safe salvage treatment, even in primary resistant T-ALL.